Penguatan Keterampilan Asertif dalam Membangun Budaya Anti-Bullying pada Sekolah Berasrama - Novi Rosita Rahmawati; Aulia Rohmawati; Sandi Ferdy Yulianto; Rahmanda Nia Limar Kinanti (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen the assertive communication skills of Islamic boarding school students (santri) as a strategic effort to build an anti-bullying culture in boarding school environments. The program was conducted at MTs and MA Arrahmah in Kediri Regency, involving 40 students residing in the dormitory. A Participatory Action Research (PAR) approach was employed to integrate problem identification, collaborative planning, action implementation, reflection, and continuous evaluation. Data were collected through focus group discussions, participatory observation, reflection sheets, pre-test and post-test instruments, as well as documentation of simulations and role-play activities. Data analysis was conducted descriptively using qualitative methods, supported by comparative analysis of pre-test and post-test results. The findings showed that prior to the intervention, student interactions were dominated by non-assertive communication patterns, such as indirect expression, silence, and normalized verbal joking. After the training, participants demonstrated improved understanding of assertive communication, as indicated by an increase in the percentage of students categorized as “clearly assertive” from 15% to 50%. This improvement was accompanied by the development of collective awareness regarding the early prevention of bullying in the boarding school environment. Therefore, the program contributed to the sustainable strengthening of students’ social relationships.